Kenya's nuclear energy dilemma. (17th December 2022) - Mbali, Kenneth Kivisi; Justus, Okonda J.
Energy is a critical component of human existence, without which no man can survive on Planet Earth. All aspects of human life have an energy input and this has become more so in today's world where technological discoveries have brought various gadgets that bring convenience to life but can only be functional if they are 'energised'. The eagerness to 'leap-frog' and attain Middle Income Status has led to great demand for more energy in Kenya. This has forced the government to explore different ways of widening the nation's energy mix, including green energy. Nuclear power can contribute to a country's energy mix and enable the bridging of existing energy gaps and thereby provide a sustainable solution to energy poverty. However, the current social-economic dynamics in Kenya may not be conducive for the country to realise its nuclear ambition.